Kecemburuan pada Laki-laki dan Perempuan dalam Menghadapi Perselingkuhan Pasangan Melalui Media Internet - Asriana, Widya; Ratnasari, Yudiana (Jurnal Psikologi: PITUTUR, 2012)
Research  on  the  type  of  infidelity  that  causes  jealousy  in  men  and women show consistent results, namely that men are more jealous of sexual infidelity  in  the  face  of  a  partner  than  women,  whereas  women  are  more jealous  in  the  face  of  emotional  infidelity  than  male  partners.  Infidelity through the internet a threat to the relationship to the individual in modern times now. Therefore, this study find out about the differences of men and women  in  the  face  of  emotional  infidelity  and  sexual  partner  through internet media. This hypothesis was tested using a forced-choice dilemmas in which participants (N = 168) were asked to choose the type of infidelityis more cause of jealousy: emotional or sexual. The results show that in the face of a partner´s infidelity via the Internet media, both men and women were  significantly  more  jealous  in  dealing  with  emotional  infidelity  than sexual infidelity. Women, when compared with men, more jealous partner in  dealing  with  emotional  infidelity,  but  there  were  no  significant differences between male and female partner´s sexual infidelity in the face.The results of this study will be discussed in the context of the theory ofevolutionary psychology. This important study carried out in order to arise the awareness that the relationship over the Internet can provide a serious effect on relationships in the real world.